Beliefs among university students towards disability: analysis of their evolution between generations - Raquel Suriá Martínez (INFAD, 2017)
Introduction. The interest to know the beliefs of students towards disability has increased in recent years. Most of the studies are of a transversal nature, and focus their efforts on the analysis of beliefs among students based on sociodemographic variables, with no focus on the study of their evolution. In order to check if attitudes evolve, the purpose of the study is to assess the attitudes of university students towards students with disabilities in different generations of students.